Factors influencing the early outcome of major lower limb amputation for vascular disease. - Campbell, W. B. (Royal College of Surgeons of England, 2001)
A consecutive series of 349 primary lower limb amputations for vascular disease, done during 1992-1998, were reviewed for amputation level, revision, complications and death, seeking associations with the American Society of Anesthesiology (ASA) grade and pre-operative co-morbidities of patients. Attempted revascularisation, and seniority of surgeon supervising the amputation were also examined for their possible influence on outcome. There were 312 patients (163 male) aged 39-92 years (median, 76 years). The majority of patients were ASA 3 or 4 (76%), and ASA 4 was associated with increased mortality (P < 0.01). Limiting heart problems (P < 0.01) and 'general frailty' (P < 0.001) also carried significantly higher risks of death, but limiting chest problems, dementia, and diabetes mellitus did not. There was no significant association between attempts at revascularisation at any time before amputation, and amputation level or the need for revision. There were no differences between consultants, registrars, and senior house officers (most senior surgeon) for any outcome measure. This study documents the medical status of amputees more clearly than usual, and demonstrates the effect of co-morbidity on the substantial mortality of these patients. The results support an aggressive policy of attempted revascularisation, and show that properly trained junior surgeons obtain satisfactory results.